A Pilot Study: Composition and Diversity of 16S rRNA Based Skin Bacterial Microbiome in Indonesian Atopic Dermatitis Population - Suwarsa O (Dove Medical Press, 2021)
Oki Suwarsa, Maryam Nissa Hazari, Hartati Purbo Dharmadji, Reiva Farah Dwiyana, Raden Mohamad Rendy Ariezal Effendi, Risa Miliawati Nurul Hidayah, Erda Avriyanti, Hendra Gunawan, Endang Sutedja Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin General Hospital, Bandung, West Java, IndonesiaCorrespondence: Hendra GunawanDepartment of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Hasan Sadikin General Hospital, Pasteur 38, Bandung, West Java, 40161, IndonesiaTel +62 222032426 ext. 3449Fax +62 222032426Email h.gunawan2016@unpad.ac.idBackground: Atopic dermatitis (AD) interferes with quality of life and is influenced by important factors like skin microbiome. The results of the skin microbiome composition and diversity in AD varied in some studies.Purpose: This study aims to determine the composition and diversity of the skin microbiome in Indonesian AD patients.Patients and Methods: Genomic deoxyribonucleic acid (DNA) preparations were obtained from skin swabs of the cubital fossa of 16 subjects, nine of which were having mild AD, three moderate AD, and four healthy individuals. DNA extraction and sequencing of the 16S ribosomal ribonucleic acid (rRNA) gene using next-generation sequencing and bioinformatics analysis were further performed.Results: Firmicutes (p), Bacilli (c), Bacillales (o), Staphylococcaceae (f), and Staphylococcus (g) were dominant in moderate AD. On the contrary, Proteobacteria (p), Gammaproteobacteria (c), Pseudomonadales (o), Moraxellaceae (f), and Acinetobacter (g) were dominant in mild AD. Staphylococcus aureus was found in the highest number in individuals with moderate AD. Interestingly, Ensifer adhaerens was found in mild AD. Microbial diversity was decreased in moderate AD.Conclusion: Metagenomic analysis in this study identified microbes in moderate and mild AD and showed a low diversity of skin microbiomes in moderate AD. Interestingly, this is the first time that the bacteria Ensifer adhaerens was detected on the human skin.Keywords: atopic dermatitis, microbiome, skin microbiome